L(P0,P1) = P0 + u(P1-P0), u = [0...1] L(P0,P1) = v(P1-P0)/2 + (P1+P0)/2, v = [-1...1]Parameterizations can be changed to lie between desired bounds. To reparameterize from u = [a...b] to w = [0...1], we can use w = (u-a)/(b-a), which gives u = w(b-a) + a. Thus, we have:
P(u), u = [a...b] = P(w(b-a)+a), w = [0...1]
A parametric cubic curve in 3D is defined by:
Usually, we consider t = [0...1].
A compact version of the parametric equations can
be written as follows:
Similarly, we can write
y(t) = T B z(t) = T CEach dimension is treated independently, so we can deal with curves in any number of dimensions.
The derivatives of the curve with respect to t can be expressed as follows:
x'(t) = [3t^2 2t 1 0] AIt is often convenient to think of the parameter t as being time in order to visualize some of the properties of the curve. The derivatives also have an intuitive interpretation in the cartesian space of the curve:
We'll first construct the cubic curve for x(t). There are four constraints that are to be met and four unknowns:
We can solve for A using A = B_inv G_x. The final equation for x is thus:
x(t) = T B_inv G_xThe matrix B_inv is often called the basis matrix, which we shall denote by M. We can thus write
x(t) = T M G_xIn this case, we have
[ -4 0 -4 4 ] M = [ 8 -4 6 -4 ] [ -5 4 -2 1 ] [ 1 0 0 0 ]Lastly, we can also write
x(t) = [ f1(t) f2(t) f3(t) f4(t) ] G_xwhere f1(t) ... f4(t) are the functions obtained from the product T M. These are functions are called the blending or basis functions, because they serve to give a weighting to the various components of the geometry vector, G. In this case, these are
f1(t) = -4t^3 + 8t^2 - 5t + 1 f2(t) = -4t^2 + 4t f3(t) = -4t^3 + 6t^2 - 2t f4(t) = 4t^3 - 4t^2 + 1,where f1(t) is the weighting function for P0, f2(t) is the weighting function for P0.5, f3(t) is the weighting function for T0.5, and f4(t) is the weighting function for P1. These basis functions look as follows:
P(t) = T M Gwhich encompasses the following three equations:
x(t) = T M G_x y(t) = T M G_y z(t) = T M G_z
Let's derive the equation for Hermite curves using the following geometry vector:
G_h = [ P1 P4 R1 R4 ]^TAs before, we'll express the curve as:
x(t) = T A_h = T M_h G_hThe constraints we'll use to define the curve are:
x(0) = P1 = [ 0 0 0 1 ] A_h x(1) = P4 = [ 1 1 1 1 ] A_h x'(0) = R1 = [ 0 0 1 0 ] A_h x'(1) = R4 = [ 3 2 1 0 ] A_hWriting these constraints in matrix form gives:
G_h = B_h A_h A_h = inv(B_h) G_h x(t) = T A_h = T inv(B_h) G_h = T M_h G_hThe inverse of B_h is thus defined as the basis matrix for the hermite curve.
[ 2 -2 1 1 ] M_h = [ -3 3 -2 -1 ] [ 0 0 1 0 ] [ 1 0 0 0 ]As before, the basis functions are the weighting factors for the terms in the geometry vector, and are given by the product T M_h. Thus, for basis functions for Hermite curves are
f1(t) = 2t^3 - 3t^2 + 1 f2(t) = -2t^3 + 3t^2 f3(t) = t^3 - 2t^2 + t f4(t) = t^3 - t^2These basis functions look as follows:
P1_h = P1 P4_h = P4 R1_h = 3 (P2 - P1) R4_h = 3 (P4 - P3)We'll arrive at the basis matrix by expressing the above in matrix form:
[ P1_h ] [ 1 0 0 0 ] [ P1 ] [ P4_h ] = [ 0 0 0 1 ] [ P2 ] [ R1_h ] [ -3 3 0 0 ] [ P3 ] [ R4_h ] [ 0 0 -3 3 ] [ P4 ] P_h = M_bh P_bThe equation for a bezier curve can thus be written as:
P(t) = T M_h M_bh P_b P(t) = T M_b P_bwhere
[ -1 3 -3 1 ] M_b = [ 3 -6 3 0 ] [ -3 3 0 0 ] [ 1 0 0 0 ]
P(t) = T M_b G_b = f1(t) P1 + f2(t) P2 + f3(t) P3 + f4(t) P4 where f1(t) = -t^3 + 3t^2 - 3t + 1 f2(t) = 3t^3 - 6t^2 + 3t f3(t) = -3t^3 + 3t^2 f4(t) = t^3 or alternatively, f1(t) = (1-t)^3 f2(t) = 3t (1-t)^2 f3(t) = 3t^2 (1-t) f4(t) = t^3
Using the Bernsteinn polynomials, we can construct a Bezier curve of
arbitrary degree. For curves of higher degree than the cubic Bezier
curve discussed thus far, we'll need more than four control points.
The general Bezier curve of degree n is given by
The basis functions are equivalent to the terms arising from the expansion of
using the binomial expansion theorem. It is also obvious from this why the sum of all the terms is equal to one.
In terms of the above figure, this means P1'=P4, R1'=k R4 . For a Bezier curve, the conditions are that the the last two points of one curve and the first two points of the second curve are aligned.
Parametric continuity of order n implies geometric continuity of order n, but not vice-versa.
Each curve segment is determined by four control points, as follows:
B-spline curves are defined by a basis matrix, just like the other types of cubic curves. We shall not discuss the derivation of this matrix here.
[ -1 3 -3 1 ] M_bspline = 1/6 [ 3 -6 3 0 ] [ -3 0 3 0 ] [ 1 4 1 0 ]where the geometry vector consists of four consecutive control points. It is easy to show that B-spline curves are C2 continuous and that they satisfy the convex-hull property. The basis functions for B-splines are as follows:
|3||G0 continuous, interpolates point|
x(t) = X(t)/W(t) y(t) = Y(t)/W(t) z(t) = Z(t)/W(t)where each of X(t), Y(t), Z(t), and W(t) are cubic polynomial curves. Defining curves as rational polynomials in this manner allows for simple exact represenations of conic sections such as circles, as well as curves which are invariant under perspective projection.